LIFE SKILL SEBAGAI LANGKAH PEMBERDAYAAN MASYARAKAT MENUJU KEMANDIRIAN EKONOMI - Ragil Atmaja; Nurlaila Nurlaila; Rahman Arif; Rahmi Atikah (Universitas Negeri Medan, 2018)
Skills education (life skill) in the context of community empowerment to prepare independent individuals so that they are empowered for their lives. Community empowerment is a process of developing, empowering, and strengthening elements of society that have low socioeconomic conditions. Empowerment activities through skills education succed in bringing individuals to become skilled in knowledge, behaviour, and organizing themselves and the social environment. This research uses a literature study approach by utilizing research results related to strategies to increase learning motivation. The literature study approach, also known as the literature study method or literature review, is a research approach that involves the analysis and synthesis of a collection of literature or written sources that are relevant to a particular research topic.